Uterine Leiomyosarcoma: A case Report - Rai, Snigdha; Shakya, Beemba (Nepal Journal of Obstetrics and Gynaecology, 2019)
Leiomyosarcoma is a rare but aggressive tumor with poor clinical outcomes in compared to other uterine cancers regardless of its stage. The preoperative diagnosis of leiomyosarcoma is seldom made as the patients present with the symptoms similar to that leiomyoma following hysterectomy and myomectomy. Herein, we present a case of a 50 years old ladyoperated for broad ligament fibroid whose histopathology and immunohistochemistry report revealed leiomyosarcoma. Keywords: fibroid, histopathology, leiomyosarcoma.